The potential of canola protein for bio-based wood adhesives - Hale, Kristen (Kansas State University, 2013)
Currently, the majority of adhesives used for wood veneer, plywood, and composite applications are formaldehyde-based. Formaldehyde is derived from petroleum and natural gas, making it non-renewable and toxic. Therefore, extensive research has been conducted to develop bio-based adhesives to replace formaldehyde-based adhesives. Soy protein has shown great potential to partially replace formaldehyde adhesives, and canola protein has similar properties to soy protein. However, little research has been conducted on the feasibility of using canola protein for wood adhesive applications. The objective of this research was to study the adhesion performance of canola protein. Canola protein was modified with different chemical modifiers including sodium dodecyl sulfate (SDS), calcium carbonate (CaCO[subscript]3), zinc sulfate (ZnSO[subscript]4), calcium chloride (CaCl[subscript]2), and 2-octen-1-ylsuccinic anhydride (OSA) as well as combined chemical modifications. The wet, dry, and soak shear strengths of the adhesive formulations were determined. Viscosity testing, differential scanning calorimetry, and TEM and SEM imaging were used to characterize protein properties. Chemical modification with SDS (1%, 3%, and 5%), CaCO[subscript]3 (1%, 3%, and 5%), ZnSO[subscript]4 (1%), and OSA (2%, 3.5%, and 5%) improved the dry and soak shear strengths compared to unmodified canola protein. Canola protein modified with 3.5% OSA had improved wet, dry, and soak shear strengths. Combined chemical modification of canola protein did not show significant improvement on shear strength. Thermal modification of canola protein adhesives showed a trend of increasing shear strength with increasing press temperature. The data suggests that with further research, canola protein has potential to be used as a commercial adhesive or as an additive to formaldehyde-based adhesives to make them more environmentally-friendly.
Keywords: Canola protein; Bio-based wood adhesives; Shear strength; Rheology; Differential scanning calorimetry; Transmission electron microscopy; Engineering, Agricultural (0539)